Odpowiedź:
[tex](-5x^{2})^{3}=-125x^{6}[/tex]
[tex]6^{6}*6^{2}:6^{3}=6^{12}:6^{3}=6^{9}[/tex]
[tex]-10^{0}=1[/tex]
[tex](\frac{16}{9})^{2}*(\frac{18}{4})^{2}=8^{2}=64[/tex]
[tex](3^{6})^{2})^{2}:3^{14}=3^{24}:3^{14}=3^{10}[/tex]
[tex]4^{2})^{3}*4^{2}:4^{3}=4^{6}*4^{2}:4^{3}=4^{8}:4^{3}=4^{5}=1024[/tex]
[tex]\frac{5^{23}}{5^{2}}=5^{23-2}=5^{21}[/tex]
[tex]-(-3)^{3}=-(-27)=27[/tex]
[tex]\frac{2^{3}}{2^{3})^{2}}=\frac{2^{3}}{2^{6}}=2^{3-6}=2^{-3}=\frac{1}{8}[/tex]
[tex](2^{16}*2^{3})^{2}=2^{19})^{2}=2^{38}[/tex]
Szczegółowe wyjaśnienie: